Decarbonization Pathways for Oil and Gas - Bassam Fattouh; Tatiana Mitrova (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2020)
The contraction in oil demand due to the spread of COVID-2019 and dissolution of the OPEC+ agreement in March have combined to generate shockwaves through the energy and financial markets. As governments all over the world grapple with one of the most severe economic crisis since the Global Financial Crisis and as the oil and gas industry is focusing on how to survive yet another extreme price cycle, some are of the view that climate change issues and decarbonization efforts will reduce in importance and may even fall off the agenda of some companies. However, energy companies have a long-term horizon, their investments extend for multiple decades and the projects planned and delivered today will go through many cycles. Over these cycles, energy companies should not be distracted from the structural trends shaping the industry. The issue of transition and decarbonization will remain dominant, driven by environmental concerns, changes in public perceptions, investors' attitudes, energy and climate policy, and the development of new technologies. In fact, one could argue that the current instability witnessed in oil markets and its underlying causes may render the oil and gas sector less attractive to investors and reinforce calls for an even faster transition from hydrocarbons. This issue of the~Forum~is focused on the potential for transformations in the oil and gas industry during the energy transition and its dramatic decarbonization.
Keywords: 330